2003
DOI: 10.1071/as03035
|View full text |Cite
|
Sign up to set email alerts
|

Short-Lived Nuclei in the Early Solar System: A Low Mass Stellar Source?

Abstract: Abstract:We discuss possible stellar origins of short-lived radioactive nuclei with meanlifeτ ≤ 100 Myr, which were shown to be alive in the Early Solar System (ESS). We first review current ideas on the production of nuclides having 10 ≤τ ≤ 100 Myr, which presumably derive from the continuous interplay of galactic astration, nucleosynthesis from massive supernovae and free decay in the interstellar medium. The abundance of the shorter lived 53 Mn might be explained by this same scenario. Then we consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 134 publications
(231 reference statements)
4
71
0
4
Order By: Relevance
“…Note that in our earlier work [97] we gave q I He /q I 0 and (N R /N I ) He in the production shells. Here we explicitly calculated the values of N R /N I and q I EN V /q I 0 in the envelope over the evolution of the star as done in [58] [201]. The values of q I EN V /q I 0 are presented in Table 3 and are shown in Fig.…”
Section: What Do Agb Stars Produce?mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in our earlier work [97] we gave q I He /q I 0 and (N R /N I ) He in the production shells. Here we explicitly calculated the values of N R /N I and q I EN V /q I 0 in the envelope over the evolution of the star as done in [58] [201]. The values of q I EN V /q I 0 are presented in Table 3 and are shown in Fig.…”
Section: What Do Agb Stars Produce?mentioning
confidence: 99%
“…A critical matter will be the nature of nucleosynthetic yields of potential sources. A recent review of the short-lived nuclei by Busso et al [58] will be used as the source for the present report. Substantial new results will be presented concerning the characteristics of AGB stars of a range in masses and with specific consideration of the results of cool bottom processing (see Section 4).…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al (1996) identified several possible target isotopes for such a study, including 60 Fe (see also Korschinek et al 1996), which is believed to be produced primarily in core-collapse and electroncapture SNe of massive stars, with mass M 8 M , via successive neutron capture on preexisting Fe isotopes, both before and during the explosion (Timmes et al 1995;Wanajo et al 2013). Other suggested sources are asymptotic giant branch (AGB; Busso et al 2003) and super-AGB (SAGB; Lugaro et al 2012) stars, as well as a rare class of high-density thermonuclear SNe (Woosley 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These findings have motivated two different kinds of explanations. The external model stipulates that the radionuclides were made in a supernova or in an asymptotic giant branch (AGB) star (e.g., Busso et al 2003). In the case of a supernova, it has been proposed that the expelled material triggered the collapse of a nearby molecular cloud core, which led to the formation of the solar system (Cameron & Truran 1977 ).…”
Section: Introductionmentioning
confidence: 99%